Indonesian Rural Women: the Role in Agricultural Development - Delima Hasri Azahari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
The women involved their roles and differing positions in society, however usually women are neglected in rural development even they experience equal status in the household decision-making process and are often described as the silent head of the home or “informal” power. Their roles in this societal context cover the spheres of human reproduction and equally important agricultural and household production, self-employment in the informal market sector and as wage laborers. The work of women and men differ yet the population is treated as one undifferentiated unit in some subsequent sections education, health and economic development. It is difficult to believe that women and men would play similar roles in economic development if their work ethic is so different. This reflected that women are not included in development planning. The reason why women excluded in development planning are they not given equivalent access to land, credit or extension services. Women also have potential to contribute to agricultural productivity beside the productivity of domestic activity is another extremely important area which should not be ignored by planners. Gender issues in development are a relatively new area of research of much importance because of its potential impact on shaping the societies of developing countries. Indonesia is in a good position to integrate rural women into development because social values in its cultures such as the Javanese already provide them with relatively egalitarian status. The lack of consideration, however, for women in the development literature reflects a need for development officials to start including them with the goal of development being one that benefit to the whole rural community. There is evidence to indicate that by eliminating barriers to women’s access to productive assets, they can fully participate and be recognized as important partners in the development process.